Role of Genomics in the Management of Hypertension - Mulatero, Paolo; Monticone, Silvia (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Arterial hypertension affects about 1 billion people worldwide and it is the strongest modifiable risk factor for cardiovascular disease and related disability. Since the initial discovery of rare monogenic disorders with large effects, the role of genomics has evolved into large genome-wide association studies detecting common variants with a modest effect size. Similarly, pharmacogenomics has emerged as a new tool for understanding variability in drug response, to maximize efficacy and reduce toxicity. This book presents the most recent advances in the field of genetics and genomics of arterial hypertension and their potential impact on clinical management. The book is a useful tool for clinicians but also to the research community and those who want to be updated in the field.